The «Arab Spring» Challenge to EU Immigration Policy - N. Makasheva К.; О. Karimsakov А. (Farabi Journal of Social Sciences, 2019)
Abstract. The events in the Arab World in 2010-2011 led to a resurgence of forced migration flows, representing a serious challenge for the Arab world, and for the European neighbors. Special depth to this surge in migration gave the revolutions in Tunisia, Egypt and Libya. This paper looks at the responses of the European Union to the challenge of European security in the context of illegal immigration and refugee flows.The method of research article is to review the events and analysis of decisions of the EU institutions against the mass flow of refugees surging into theeffects of the «Arab Spring». Analysis of the responses taken by the EU reveals the fullness of the impact of the «Arab Spring» not only on external but also internal security.The focus of the paper lies on the EU search for tactical decisions and their effectiveness during the migration crisis. Summarizing the article, we came to the following conclusion: adopted short-term measures aimed at resolving problems connected with the influx of refugees have not been successful, because the situation got out of control of the EU authorities. Furthermore, the proposal to resolve the migration crisis through the «soft» tool has undermined the unity of the member states.